Considerations on bone growth and development processes at the dento-maxillary level (in Romanian) - Grigorescu Catalin Cicerone; Stanciu Dan; Stanciu Radu; Temelcea Anca (Medicamentul Veterinar, 2014)
Facial development is the result of growth and skeletal modeling for every component skeletal and /or/functional, both together or in part, of his power and the proliferation of multiple influences which shall be exercised on them. Taking into account the myriad factors affecting facial development can be explained the large variety of individuals, and also, the large amount of dento-maxillary anomalies. Essential aspects in this topic are presented schematically in this mini-review.